Publications of Easy-to-Read Foundation in Sweden - Tronbacke, Bror (Information & Media, 1996)
November 8-10, 1996, Bror Tronbacke, director of LL-Stiftelsen (the Easy-to-Read Foundation), Sweden, gave the lecture, The Publications of Easy-to-Read Foundation in Sweden at the Faculty of Communication, University of Vilnius, for the Faculty members, students, and librarians from some Vilnius libraries. The author gave permission to translate his lecture and to publish it in the Lithuanian professional press. Easy-to-Read texts have been published since 1968. There is fiction and non-fiction, special titles and adaptations of classics: novels, short-stories, thrillers, poetry, travel books, etc. For the last ten years, the Easy-to-Read newspaper, 8 SIDOR (8 pages), has been published. Since 1987, LL-Stiftelsen has been entrusted with making news and literary works easy to read and understand for people with reading difficulties or limited literacy and language skills. These activities are a part of the Swedish cultural policy. It is a democratic right that everyone has access to culture, literature, and information - in a comprehensible form. It is of central importance that everyone is able to receive information about what is going on in society. People must be well informed to be able to exercise their democratic rights and influence their own lives. Insights provide the basis for opinions. It is also a matter of quality of life. The ability to read independently gives one self-confidence, and the possibility to expand one’s world view and to develop one’s own life. It is, therefore, extremely important that handicapped people or those unused to reading can get the special materials which can help them improve their reading skills, in order to become more self-confident, provide them with cultural heritage, news information, and to integrate them into society.